Istikhdām Biṭāqah al-Mufradāt Litanmiyyah Mahārah al-Qirā’ah biṭarīqah “Unẓur wa Qul” - Ratnasari, Kartika (Study Program of Arabic Language Teaching, 2021)
Arabic Language learning is now highly improved by Islamic and general schools. Certainly, the way of improvement needs a special method in its teaching to be gained well by the beginner of this study. From the interview done by the researcher, students of the first grade of Junior High School had very low Arabic reading ability so that they need certain teaching methods to equip them with good ability in Arabic reading skills. To overcome this problem, the researcher applied a teaching method by using vocabulary adapted from the “Look and Say” method by considering that this card is one of the media to improve the reading ability of students in the teaching process. This research focused on the effectiveness of vocabulary cards in improving reading ability in makhraj huruf pronunciation, vocabulary meaning mastery, type of sentence understanding, and word context understanding. This research used classroom action research which consists of two cycles in which every cycle has four steps: planning, action, observation, and reflection. The population of this research is the first grade of Junior High School students. The results of this research showed that vocabulary card application can increase their reading ability from their makhraj huruf pronunciation of vocabulary, vocabulary meaning mastery through its picture, sentence type understanding in jumlah ismiyah with ism isyarah, vocabulary context understanding which consists of shifah maushufah.